Prospects for comparing European hospitals in terms of quality and safety: lessons from a comparative study in five countries. - Burnett, S; Renz, A; Wiig, S; Fernandes, A; Weggelaar, A; Calltorp, J; Anderson, J; Robert, G; Vincent, C; Fulop, N (2013)
PURPOSE: Being able to compare hospitals in terms of quality and safety between countries is important for a number of reasons. For example, the 2011 European Union directive on patients' rights to cross-border health care places a requirement on all member states to provide patients with comparable information on health-care quality, so that they can make an informed choice. Here, we report on the feasibility of using common process and outcome indicators to compare hospitals for quality and safety in five countries (England, Portugal, The Netherlands, Sweden and Norway). MAIN CHALLENGES IDENTIFIED: The cross-country comparison identified the following seven challenges with respect to comparing the quality of hospitals across Europe: different indicators are collected in each country; different definitions of the same indicators are used; different mandatory versus voluntary data collection requirements are in place; different types of organizations oversee data collection; different levels of aggregation of data exist (country, region and hospital); different levels of public access to data exist; and finally, hospital accreditation and licensing systems differ in each country. CONCLUSION: Our findings indicate that if patients and policymakers are to compare the quality and safety of hospitals across Europe, then further work is urgently needed to agree the way forward. Until then, patients will not be able to make informed choices about where they receive their health care in different countries, and some governments will remain in the dark about the quality and safety of care available to their citizens as compared to that available in neighbouring countries.